The Coffee Business Management with Islamic Symbols: Total Motivation Model and Shari’ah Enterprise Theory Approach - Novi Puspitasari (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2022)
There is a coffee product under the brand BIKLA. This coffee is produced by the Pesantren (Islamic boarding school) cooperative located in Bangsalsari District, Jember Regency. This coffee is unique because on the front packaging it says "Barokah Ibrahimy", while on the back packaging it says "Barokah Rotibul Haddad from the students (santri). The purpose of this research is (1) exploring the application of business management in BIKLA coffee company; (2) explore the alignment of the implementation of business management in BIKLA coffee company with Total Motivation Model and Shari’ah Enterprise Theory. This research uses qualitative methods with a case study approach. Data is obtained by in-depth interviews and observations. The results showed that the company implemented collaborative business management, namely the merger of business management aimed for commercial and afterlife for production activities, human resource management, marketing, and finance. The application of business management on BIKLA coffee company can be in line with Shari’ah Enterprise Theory and with the Total Motivation Model